Isolated voices: Older adults’ reflections on packaging use and accessibility during lockdown - Yoxall, Alaster (RChD: creación y pensamiento, 2020)
Packaging used by older adults is a complex, multifaceted event. It is a complex multifaceted event in normal times. As we age, our strength, dexterity and cognitive ability all naturally decline, and we are more likely to be ill. Isolated and removed from normal support networks, many older adults would have to adapt in order to access food. Previous work by the author showed that the influences of purchase could be split into three areas: packaging attributes such as size, shape or weight, familiarity indicating whether a person had bought the brand be- fore, and environmental factors such as the weather, that affect the ability to shop or the proximity of family or friends. This small study of 30 respondents showed that the Covid-19 pandemic distorted these influences for all the respondents, reducing their opportunity for choice and increasing their reliance on others. In earlier work, the author had split the coping strategies to deal with these physical (the use of knives, etc.) and emotional (the use of relatives, friends, etc.) issues. The pandemic also increased the need for these strategies where respondents had to use knives on unfamiliar items or use ad hoc support networks such as asking for a tin opener through a window.